The Psychometric Properties of the Norwegian version of Bayley Scales of Infant and Toddler Development (BSID, BSID-II, BSID-III) - Richter, Jörg; Valla, Lisbeth (PsykTestBarn, 2013)
Description: The Bayley Scales of Infant Development (BSID) measure cognitive, language and motor developmental functioning, including social and emotional behaviour in infants and toddlers aged 1 to 42 months. They have been revised twice, and its third edition, BSID-III represents the version that currently should be used. BSID-III consists of five subtests that are subsummed into three scales and three questionnaires. However, only the three core scales (cognitive, motor, and language scale) are included in the Norwegian edition. To administer this test takes about 30 to 50 minutes dependent on the child’s age. The Norwegian edition of BSID is available from Pearson Assessment and Information AB. Literature search: Our systematic literature search identified 147 references, of which seven publications were derived from five Norwegian clinical studies and one Danish general population study (eight articles were based on BSID, 16 were based on BSID-II, and two were based on BSID-III). Psychometrics: There is no available evidence of the psychometric properties of the Norwegian or Scandinavian versions of the BSID-III. Only one Norwegian study reported predictive validity related to the psychomotor developmental index (PDI) based on Norwegian BSID data. It was concluded that the PDI represents an effective diagnostic instrument because of a relatively large area under the curve (AUC) in the receiver operating characteristics (ROC) curve analysis. None of the Norwegian or Scandinavian studies investigated or reported reliability measures for the BSID-II. Norwegian or other Scandinavian norms are not available. Conclusion: There is no evidence of the psychometric properties related to the Norwegian or other Scandinavian versions of BSID-III. There is an urgent need for studies of psychometric properties in Norwegian samples. The American norms have to be applied cautiously in the evaluation of the evaluation of Norwegian children.